1987
DOI: 10.1002/chin.198704211
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: The Mechanism of Action of the Gastric Acid Secretion Inhibitor Omeprazole.

Abstract: 211ChemInform Abstract Omeprazole (I) is transformed by gastric acid, producing a mixture of the isomeric thiadiazine derivatives (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 1 publication
2
70
1
Order By: Relevance
“…The pKa2 determines the activation rate of PPIs and affects the stability of acid suppression. The active form of the drug forms covalent disulphide bonds with cysteines accessible from the exoplasmic surface of the enzyme thus inhibiting it; studies by Sachs et al showed that proton pump inhibition is not irreversible (9)(10)(11)(12)(13)(14).…”
Section: Mechanism Of Action Of Ppismentioning
confidence: 99%
“…The pKa2 determines the activation rate of PPIs and affects the stability of acid suppression. The active form of the drug forms covalent disulphide bonds with cysteines accessible from the exoplasmic surface of the enzyme thus inhibiting it; studies by Sachs et al showed that proton pump inhibition is not irreversible (9)(10)(11)(12)(13)(14).…”
Section: Mechanism Of Action Of Ppismentioning
confidence: 99%
“…37 This would involve the rearrangement of the PPI to form a permanent action with the N of the pyridine now linked directly to the 2C of the benzimidazole (please see below). The protonation of the pyridine moiety was accepted for many years as the protonation reaction that initiated activation of the PPIs, [37][38][39] but the experiments on this were performed initially at acidic pH and with high cysteine concentrations present and omeprazole was the only PPI on which these experiments were performed. With the introduction of other PPIs with generally similar pyridine pK a s, different rates of activation were found which cannot be explained as being due to the pyridine.…”
Section: Hk Atpase Inhibitors Ppismentioning
confidence: 99%
“…It was postulated that this class of compound acted as a prodrug that only reacted with the ATPase after this acid catalyzed conversion to an active form, perhaps the sulfenic acid or sulfenamide [33,34]. Later, it was shown that the final structure generated in acidic solutions was a rearranged planar tetracyclic compound containing a highly -SH reactive sulfenamide group [35]. It is not clear whether the sulfenic acid or its dehydro form, the sulfonamide is responsible for covalent binding to the H,K-ATPase.…”
Section: The Proton Pump Inhibitorsmentioning
confidence: 99%
“…These active forms, either the cyclic sulfenamide or the sulfenic acid is very reactive with the thiol groups of cysteine which can then form a disulfide bond with inhibition [35].…”
Section: Cellular Mechanismmentioning
confidence: 99%